Optimizing Power Generation from Building Ventilation Systems: A Study on Exhaust Fan Efficiency - Samriddhi Saini; Rajesh Kumar; Priyanshu Sharma; Sandeep Upadhyay; Lovesh Jain (International Journal of Electrical Power and Machine Systems, 2024)
Due to population growth, the world's energy consumption has increased dramatically in both wealthy and developing nations in recent years, and by 2042, it is predicted to have doubled or more. Since a few years ago, the use of innovative sustainable power sources to meet energy demands has been gradually increasing. We've chipped away at a different idea because of this. As an alternative energy source, renewable energy (RE) resources are crucial in reducing reliance on fossil fuels to produce electricity. To increase the efficiency of RE resources for energy generation, extensive study has been conducted recently, as highlighted by a number of researchers. From a socioeconomic standpoint, the rate of population growth in the globe today suggests that there will likely be an increase in energy demand because energy consumption is strongly correlated with both economic development and overall population in a nation.In contemporary automobile engines, the exhaust gas contains a significant amount of thermal energy. In a car, two thirds of the energy produced during combustion is wasted as waste heat, of which hot exhaust gas makes up 40%. the most recent advancements and technology in internal combustion engine (ICE) exhaust gas waste heat recovery. These include six-stroke cycle internal combustion engines, organic rankine cycles (ORCs), thermoelectric generators (TEGs), and recent advancements in turbocharger technology. One of the biggest and most amazing new automotive waste heat recovery technologies that has a lot of potential is the thermoelectric generator (TEG). A thermoelectric power generator is a solid-state device that directly converts thermal energy—heat—resulting from a temperature differential into electrical energy by means of the "Seebeck effect". The thermoelectric power cycle, which closely resembles the power cycle of a conventional heat engine and follows the fundamentals of thermodynamics, uses charge carriers, or electrons, as the working fluid. This research offers an original approach for generating power using exhaust fans, which are renewable energy sources makes it critical to investigate unorthodox power generating methods. In order to transform the rotary energy of the fan blades into electrical power, the idea entails retrofitting current exhaust fan systems with a generator mechanism. The research approach combines computational simulations, theoretical analysis, and experimental validation. Firstly, theoretical calculations are performed to estimate the potential power output based on the airflow rate and rotational speed of the fan. Computational fluid dynamics (CFD) simulations are then utilized to model the airflow patterns within the exhaust system and optimize the design for maximum energy extraction. Ultimately, in order to confirm the viability and effectiveness of the suggested power generation technique, experimental testing is carried out with prototype installations. The results demonstrate the viability of generating significant amounts of electricity from exhaust fans, with efficiency levels comparable to other small-scale renewable energy systems. Furthermore, the environmental impact assessment reveals that utilizing exhaust fan power generation can contribute to reducing carbon emissions and mitigating the ecological footprint associated with traditional energy sources. In addition to its environmental benefits, the economic analysis highlights the cost-effectiveness of integrating exhaust fan power generation into existing infrastructures. The initial investment for retrofitting exhaust fans with generator systems is offset by long-term energy savings and potential revenue generation through excess electricity sales or incentives from utility companies
Keywords: Amplifier; Dynamo; exhaust and turbine; revolutions per minute (R.P.M)